A Cross-Sectional Survey on the Impact of Irrelevant Speech Noise on Annoyance, Mental Health and Well-being, Performance and Occupants’ Behavior in Shared and Open-Plan Offices - Di Blasio, Sonja; Shtrepi, Louena; Puglisi, Giuseppina Emma; Astolfi, Arianna (International journal of environmental research and public health, 2019)
This cross-sectional survey has compared subjective outcomes obtained from workers in shared (2–5 occupants) and open-plan (+5 occupants) offices, related to irrelevant speech, which is the noise that is generated from conversations between colleagues, telephone calls and laughter. Answers from 1078 subjects (55% in shared offices and 45% in open-plan offices) have shown that irrelevant speech increases noise annoyance, decreases work performance, and increases symptoms related to mental health and well-being more in open-plan than in shared offices. Workers often use headphones with music to contrast irrelevant speech in open-plan offices, while they take a break, change their working space, close the door or work from home in shared offices. Being female, when there are more than 20 occupants, and working in southern cities without acoustic treatments in the office, make it more likely for the occupants to be annoyed by irrelevant speech noise in open-plan offices. While, working in southern cities and with acoustic treatments in the office makes it more likely that noise annoyance will be reported in shared offices. Finally, more than 70% of the interviewed in open-plan offices were willing to reduce their voice volumes when advised by a noise monitoring system with a lighting feedback.